Eating the honey of words new and selected poems - Bly, Robert (Perennial, 2000)
Robert Bly has had many roles in his illustrious career. Now, in Eating the Honey of Words, he presents the best poems he has written in the last three decades, including favorites from his earlier books such as Silence in the Snowy Fields, The Man in the Black Coat Turns, and Loving a Woman in Two Worlds. Joining these timeless classics are a number of poems from these past decades never published before, as well as a complete section of new poems from the last two years.